Dual-band Via-less Band-pass Filter Based on Cascaded Closed Ring Resonator - Teguh Firmansyah; Supriyanto Praptodiyono; Achmad Rifai; Syah Alam; Ken Paramayudha (National Research and Innovation Agency, 2023)
A band-pass filter (BPF) is an essential part of a wireless communication system as it functions to reduce interference and noise. Many structures have been proposed to achieve a high-quality BPF. Typically, these structures utilize vias. However, vias has several drawbacks, including impedance discontinuities, increased resistance values, and complex structures. In this study, we propose a dual-band BPF based on a cascaded closed ring resonator (CCRR) without using vias. Specifically, the proposed structure consists of multiple CCRRs connected at the corner pattern and incorporates capacitive coupling to the input impedance. Additionally, the CCRR configuration has dual sizing to achieve dual-band performance. Subsequently, the proposed BPF is simulated and fabricated using Duroid Rogers RT 5880 with dielectric constant εr = 2.2, dissipation factor tan δ = 0.0009, and thickness h = 1.575 mm. The measurement results demonstrated that the dual-band BPF operated at a resonant frequency of 2.50 GHz with a transmission coefficient (S21) value of -2.18 dB in the first band. In the second band, a resonant frequency of 3.70 GHz was obtained with an S21 value of -1.43 dB. The bandwidth in the first band was 160 MHz, and in the second band, it was 110 MHz. Moreover, based on the measurement results, the reflection coefficient (S11) in the first band was -11.05 dB, while in the second band, it was -23.3 dB. The excellent agreement between the simulation and measurement validates the proposed method.